2010
DOI: 10.1007/s00011-010-0163-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum amyloid A and obesity: a meta-analysis and systematic review

Abstract: A strong association between body mass index and SAA levels was found in the 11 cross-sectional studies. The overall correlation coefficient is 0.230 (95% CI 0.160-0.297, P < 0.0005). The ten prospective studies were subsequently analyzed, and the difference in SAA levels before and after weight loss, expressed as standardized mean difference was -0.480 (95% CI -0.678 to -0.283, P < 0.0005). We discuss some potential underlying mechanisms and clinical applications for reducing SAA levels in obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
65
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 90 publications
(148 reference statements)
8
65
1
1
Order By: Relevance
“…Increased SAA expression in subcutaneous white adipose tissue can result in increased circulatory levels of SAA (29). The epidemic of obesity is accompanied by an increase in atherosclerotic diseases and may have a close association with SAA levels (30). The increase in adiposederived SAA in obesity may be a mechanistic link between obesity and accelerated atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Increased SAA expression in subcutaneous white adipose tissue can result in increased circulatory levels of SAA (29). The epidemic of obesity is accompanied by an increase in atherosclerotic diseases and may have a close association with SAA levels (30). The increase in adiposederived SAA in obesity may be a mechanistic link between obesity and accelerated atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…SAA is an acute-phase protein and primarily synthesized in the liver in response to proinflammatory stimuli. Interleukin 1(IL-1), IL-6, and tumor necrosis factor (TNF)-α could induce SAA production [8]. HSP is a systematic inflammatory disease and nonspecific proinflammatory cytokines, such as TNF-α, IL-6, IL-1, and IL-8, were reported to be higher in acute HSP than in convalescent stage and healthy controls [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Serum amyloid A (SAA) is an acute-phase reactant whose level in the blood markedly increases in response to various stimuli [8]. Expression studies showed local production of SAA proteins in atherosclerotic lesions, Alzheimer brain tissues, inflammatory tissues, tumor tissues, and rheumatoid arthritis [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…This is important because obesity is characterized by adiposopathy and increased inflammation (8). One molecule that is released from hypertrophic adipocytes and that has been shown to predict CVD, is serum amyloid-A (SAA) (9,10). Furthermore, SAA has been suggested as a candidate molecule linking increased fat load and its comorbidities (11).…”
mentioning
confidence: 99%